Correlation of physicochemical properties with antioxidant activity in phenol and thiophenol analogues - R. Bernadett Vlocskó; Maxim Mastyugin; Béla Török; Marianna Török (Scientific Reports)
Abstract Oxidative stress, associated with excessive production of reactive oxygen and nitrogen species (ROS, RNS), contributes to the development and progression of many ailments, such as aging, cardiovascular diseases, Alzheimer’s disease, Parkinson’s disease, diabetes, cancer, preeclampsia or multiple sclerosis. While phenols and polyphenols are the most studied antioxidants structurally similar compounds such as anilines or thiophenols are sporadically analyzed despite their radical scavenging potential. This work assesses the impact of structural features of phenols and thiophenols on their antioxidant activity. Seventeen pairs of phenol/thiophenol analogues, possessing both electron-donating and withdrawing groups were selected for this study. Several physicochemical properties of the compounds were determined by density functional theory (DFT) calculations at the (U)B3LYP/6-311++G(d,p) level of theory for gas phase calculations and at the (U)B3LYP/6-311++G(d,p) scrf = (smd, solvent = water) level for the solvated ones. Correlations between calculated properties and experimental radical scavenging activities were investigated to identify the pivotal physical characteristics contributing to antioxidant efficiency. These include S–H and O–H bond distances and bond dissociation enthalpies (BDE), dipole moments, logP values, highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) orbital energies, and the HOMO–LUMO gap energies that were calculated at the M06-2X/6-311++G(d,p) level of theory, and Fukui functions. The experimental activity was evaluated using the 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and 2,2-diphenyl-1picrylhydrazyl (DPPH) radical scavenging assays. Several compounds exhibited superior scavenging abilities, surpassing that of the reference antioxidant Trolox. The extensive DFT calculations revealed that in the gas phase, lower BDE values, compared to IP and PA, suggested that the HAT mechanism predominates in case of these compound groups. In contrast, in water, significant reductions in PA due to solvent effects suggested that the SPLET mechanism is dominant under aqueous conditions.